1. Solve one of the equations for one variable in terms of the other variable.
-7x - 2y = -13
Solving for x:
x = (2y - 13) / -7
2. Substitute the expression for the variable in the other equation.
x - 2y = 11
Substituting (2y - 13) / -7 for x:
(2y - 13) / -7 - 2y = 11
3. Simplify the equation by expanding and combining like terms.
(2y - 13) / -7 - 2y = 11
(2y - 13 - 14y) / -7 = 11
(-12y - 13) / -7 = 11
4. Solve the equation for the remaining variable.
(-12y - 13) / -7 = 11
-12y - 13 = 11 * -7
-12y - 13 = -77
-12y = -77 + 13
-12y = -64
y = -64 / -12
y = 16/3 or approximately 5.33
5. Substitute the value of y into one of the original equations.
x - 2(16/3) = 11
x - 32/3 = 11
x = 11 + 32/3
x = 33/3 + 32/3
x = 65/3 or approximately 21.67
6. Write the solution as an ordered pair (x, y).
Solution: (65/3, 16/3) or approximately (21.67, 5.33)
Put the 10 steps in order that are used to solve the following systems of equations by substitution. and put what the answer whould be for each step
−7x−2y=−13 x−2y=11
1 answer